Performance of Pharmaceutical Companies in India A Critical Analysis of Industrial Structure, Firm Specific Resources, and Emerging Strategies - Mazumdar, Mainak; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2013)
This book explains how government support and institutional set up facilitated the evolution of the Indian pharmaceutical industry and provides an economic analysis of firm strategies due to recent policy changes. The book is useful for researchers interested in understanding the transition of a lifeline sector for an emerging economy like India. Students of public policy, health administrators and health economists who are interested in the functioning of the pharmaceutical sector that produces life saving drugs in developing nations will find this book useful. The book also provides good coverage on data envelopment analysis (DEA), a useful technique for understanding productivity and efficiency. It can provide guidance to the research students on the applicability of DEA technique to address various research questions for analysis. The book will be a valuable addition to libraries in colleges of pharmacy and medicine as well as to all other academic and research centers.
An Overview of the Pharmaceutical Sector in India -- The sources of Heterogenity in the Efficiency of Indian Pharmaceutical Firms -- Comparing Efficiency Across Various Groups of Firms: A Meta-Frontier Approach -- Examining the Efficiency, Technical, and Productivity Changes of the Indian Pharmaceutical Firms: A Malmquist-Meta Frontier Approach -- Profitability of the Indian Pharmaceutical Firms -- The Problem of Availability of Patented Drugs due to Product Patent and Parallel Trade: A Theoretical Approach -- Conclusions and Policy Implications.
Keywords: Industries; Industrial organization; Public health; Social policy; Pharmacy; Industries; Industrial Organization; Public Health; Social Policy; Pharmacy